2009
DOI: 10.1056/nejmoa0808710
|View full text |Cite
|
Sign up to set email alerts
|

IDH1andIDH2Mutations in Gliomas

Abstract: BACKGROUND A recent genomewide mutational analysis of glioblastomas (World Health Organization [WHO] grade IV glioma) revealed somatic mutations of the isocitrate dehydrogenase 1 gene (IDH1) in a fraction of such tumors, most frequently in tumors that were known to have evolved from lower-grade gliomas (secondary glioblastomas). METHODS We determined the sequence of the IDH1 gene and the related IDH2 gene in 445 central nervous system (CNS) tumors and 494 non-CNS tumors. The enzymatic activity of the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

205
4,436
26
74

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 5,121 publications
(4,843 citation statements)
references
References 21 publications
205
4,436
26
74
Order By: Relevance
“…Isocitrate dehydrogenase gene mutations, estimated to occur in 70–90% of diffuse lower grade gliomas, are strongly implicated in both tumourigenesis and prognosis 23, 24, 25. Loss of heterozygosity of 1p19q, was occurred in 60–80% of oligodendroglioma and up to 45% of oligoastrocytoma 26.…”
Section: Discussionmentioning
confidence: 99%
“…Isocitrate dehydrogenase gene mutations, estimated to occur in 70–90% of diffuse lower grade gliomas, are strongly implicated in both tumourigenesis and prognosis 23, 24, 25. Loss of heterozygosity of 1p19q, was occurred in 60–80% of oligodendroglioma and up to 45% of oligoastrocytoma 26.…”
Section: Discussionmentioning
confidence: 99%
“…Isocitrate dehydrogenase 1 and 2 (IDH1/2) mutations are recognized as definitive diagnostic molecular biomarkers of secondary GBM and are more prognostically valuable than the history of tumor onset 3. Correspondingly, wild‐type IDH1/2 genotypes are considered robust biomarkers of primary GBM (<5%) 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of recurrent somatic point mutations in IDH1 was first identified in 12% of all adult glioblastoma tumors by high‐throughput DNA sequencing 51. Deep sequencing further revealed that mutated IDH1 and IDH2 occur in a high proportion (>70%) of low‐grade (grade II–III) astrocytomas and oligodendrogliomas and secondary glioblastoma 51, 52, 88, 89. Since these initial reports, mutations in IDH1 and IDH2 have also been found in other diverse cancers including 16–17% of patients with AML,53 20% of patients with angioimmunoblastic T‐cell lymphomas,90 and more rarely in cholangiocarcinomas,91 breast carcinomas,92 acute lymphoblastic leukemias,93 prostate cancer,93 osteosarcoma,94 and others 53, 91, 92, 93, 95, 96, 97.…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 99%
“…It appears that the removal of the arginine, rather than the substitution of a specific residue, is the critical feature of this mutation, although the most frequent replacement observed is a histidine residue (R132H) 51, 52, 93, 98. Mutations in IDH2 in gliomas occur at a much lower frequency (0–6%) than IDH1 88 in the paralogous amino acid residue—R140—but also at R172.…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 99%
See 1 more Smart Citation